Applicability of Deep Eutectic Solvents inÂ Oil and Gas Processing Fields for CO2 Control - Haq, I.U. (John Wiley and Sons Inc, 2022)
Anthropogenic greenhouse gas emissions, particularly CO2 emissions, have grown substantially, posing environmental challenges that affect mankind and ecosystems. As a possible consequence, carbon capture and storage is a viable solution to this worldwide problem. However, some aqueous solvents have been applied to capture greenhouse gases, though they are not environmentally benign. Deep eutectic solvents (DESs) emerged as a unique choice according to research into greener solvents for this activity. The applications of DESs and the gas solubility of various DESs with emphasis on CO2 solubility in the oil and gas field are evaluated. This innovative solvent is also described in terms of its preparation and chemical composition. Detailed literature on investigation of CO2 solubility in DESs based on experimental data is included. Â© 2022 Wiley-VCH GmbH.